2016
DOI: 10.1136/bmjopen-2016-013014
|View full text |Cite|
|
Sign up to set email alerts
|

Study protocol for Chronic Obstructive Pulmonary Disease-Sitting and ExacerbAtions Trial (COPD-SEAT): a randomised controlled feasibility trial of a home-based self-monitoring sedentary behaviour intervention

Abstract: IntroductionAn acute exacerbation of chronic obstructive pulmonary disease (COPD) marks a critical life event, which can lower patient quality of life and ability to perform daily activities. Patients with COPD tend to lead inactive and highly sedentary lifestyles, which may contribute to reductions in functional capacity. Targeting sedentary behaviour (SB) may be more attainable than exercise (at a moderate-to-vigorous intensity) for behaviour change in patients following an exacerbation. This study aims to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The study design was a 3-armed feasibility randomized controlled trial (RCT) lasting 2 weeks following discharge from hospital, with 1:1:1 allocation. A detailed description of the study protocol has been published previously [ 15 ].The trial is reported in accordance with CONSORT-EHEALTH ( Multimedia Appendix 1 ). The study was approved by Research Ethics Committee East Midlands Leicester Central and all participants provided written informed consent (15/EM/0433).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design was a 3-armed feasibility randomized controlled trial (RCT) lasting 2 weeks following discharge from hospital, with 1:1:1 allocation. A detailed description of the study protocol has been published previously [ 15 ].The trial is reported in accordance with CONSORT-EHEALTH ( Multimedia Appendix 1 ). The study was approved by Research Ethics Committee East Midlands Leicester Central and all participants provided written informed consent (15/EM/0433).…”
Section: Methodsmentioning
confidence: 99%
“…Deliveries of the Education and Education+Feedback components of the intervention were audio recorded. Details of the intervention components (education booklet, application, and vibration prompts) have been previously reported [ 15 ]. Each component was coded separately by 2 trained, independent assessors using dichotomous scales (present or absent) for consistency and ordinal scales (poor, adequate, or excellent) for quality of delivery.…”
Section: Methodsmentioning
confidence: 99%
“… 11 A simple search for studies exploring the effects of interventions specifically targeting time spent in sedentary behaviour identified a single protocol. 76 Similarly, while poor sleep quality is commonly reported by people with COPD 15 , 77 and has demonstrated associations with adverse physiological and psychological health outcomes, 14 16 few studies have explored therapeutic interventions to improve sleep in people with COPD without a coexisting sleep disorder. 78 81 …”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the study protocol has been published previously [15].The trial is reported in accordance with CONSORT-EHEALTH (Multimedia Appendix 1). The study was approved by Research Ethics Committee East Midlands Leicester Central and all participants provided written informed consent (15/EM/0433).…”
Section: Designmentioning
confidence: 99%